The moonshot phenomenon in the business world - Kiril Dimitrov (11th International Conference On Application Of Information And Communication Technology And Statistics In Economy And Education (ICAICTSEE – 2021), 2023)
This paper reviews basic and emerging research trends on the moonshot phenomenon in the business world. It traces the emergence and development of the nuances for this construct, its relationships with the proclaimed corporate culture and some new attributes of management by objectives. Nevertheless the numerous realizations that the moonshot phenomenon has acquired – as goals, projects, tasks, specific leadership, skill and others, it seems subordinated to certain principles and approaches, constituting the so called moonshot thinking that is also succinctly described.
https://icaictsee.unwe.bg/past-conferences/ICAICTSEE-2021.pdf
Keywords: M14; L1; L2; 650; moonshot; corporate culture; proclaimed corporate culture; strategic management; exponential organizations